lumi68
Answered

At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Solve the equation 4y^2=15+7y and hence solve the equation 4(9^x)=15+7(3^x)

Sagot :

9514 1404 393

Answer:

  • y = -5/4, 3
  • x = 1

Step-by-step explanation:

a) The equation written in standard form is ...

  4y^2 -7y -15 = 0

We find the two factors of (4)(-15) that have a sum of -7 to be -12 and +5. Then the equation can be written and factored as ...

  4y^2 -12y +5y -15 = 0

  4y(y -3) +5(y -3) = 0

  (4y +5)(y -3) = 0

The solutions to this equation are the values of y that make the factors zero:

  4y +5 = 0   ⇒   y = -5/4

  y -3 = 0   ⇒   y = 3

__

b) Let y = 3^x. Then the equation transforms to ...

  4((3^x)^2) = 15 +7(3^x)

  4y^2 = 15 +7y . . . . . . . . . same equation as above, with the same solutions

Then the value of x is ...

  log(y) = x·log(3)

  x = log(y)/log(3) . . . . . . . . y > 0

The only useful solution of the ones found above is y = 3.

  x = log(3)/log(3)

  x = 1

View image sqdancefan
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.